Near‐infrared spectroscopy is a promising noninvasive technique for monitoring the effects of feeding regimens on the cerebral and splanchnic regions. (24th October 2017) - Grometto, Alice; Pizzo, Benedetta; Strozzi, Maria Chiara; Gazzolo, Francesca; Gazzolo, Diego
Abstract: Aim: The effects of different milk and, or, administration regimens on cerebro‐splanchnic perfusion are still a matter of debate. We investigated the effects of the bolus administration of breast milk or formula on cerebro‐splanchnic oximetry, function and perfusion, assessed by near‐infrared spectroscopy (NIRS). Methods: This observational study of 30 infants fed with breast (n = 15) or formula (n = 15) milk, and matched for gestational age and birth weight, was carried out in the neonatal intensive care unit of the C Arrigo Children's Hospital, Alessandria, Italy, a tertiary‐level referral centre, from October 2015 to December 2016. NIRS monitoring parameters, such as cerebral and splanchnic oximetry, fraction of tissue oxygen extraction and the cerebral–splanchnic ratio, were recorded before, during and after feeding. Results: Breast milk led to a significant increase in cerebro‐splanchnic oximetry and tissue oxygen extraction (p < 0.001) during and after feeding, and the cerebro‐splanchnic perfusion ratio was significantly higher (p < 0.001) in the breast than formula group. Conclusion: Our study results suggest that breast milk was better tolerated than formula, requiring lower energy expenditure and lower cerebro‐splanchnic haemodynamic redistribution. The findings could prompt investigations using NIRS as a promising noninvasive tool for cerebral and splanchnic longitudinal monitoring during neonatal feeding.